2003
DOI: 10.1002/mrd.10255
|View full text |Cite
|
Sign up to set email alerts
|

Development of the signalling pathways associated with sperm capacitation during epididymal maturation

Abstract: As spermatozoa mature within the epididymis they acquire the potential for capacitation and ultimately fertilization. In biochemical terms, the former is reflected in the progressive activation of a signal transduction pathway characterized by cAMP-mediated induction of phosphotyrosine expression on the sperm tail. In this study, we have examined the cellular mechanisms controlling this maturational event. Caput epididymal spermatozoa exhibited tyrosine phosphorylation on the sperm head that was largely unresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
1
12
2
Order By: Relevance
“…This result differs Ϫ HCO 3 from that of Baker et al [20], who found that, in the absence of , protein tyrosine phosphorylation in the rat Ϫ HCO 3 did not return to control levels even after exposure of spermatozoa to a maximal dbcAMP-plus-PTX stimulus. Thus, although these authors proposed that the factor responsible for this failure is low intracellular pH, our results support the notion that, in the rat, like in the mouse, the effect of on protein tyrosine phosphorylation likely results Ϫ HCO 3 from the ability of the anion to regulate the sperm adenylyl cyclase [17].…”
contrasting
confidence: 82%
See 1 more Smart Citation
“…This result differs Ϫ HCO 3 from that of Baker et al [20], who found that, in the absence of , protein tyrosine phosphorylation in the rat Ϫ HCO 3 did not return to control levels even after exposure of spermatozoa to a maximal dbcAMP-plus-PTX stimulus. Thus, although these authors proposed that the factor responsible for this failure is low intracellular pH, our results support the notion that, in the rat, like in the mouse, the effect of on protein tyrosine phosphorylation likely results Ϫ HCO 3 from the ability of the anion to regulate the sperm adenylyl cyclase [17].…”
contrasting
confidence: 82%
“…Adenylyl cyclase, the enzyme responsible for cAMP synthesis, is markedly stimulated by physiologically relevant Ϫ HCO 3 concentrations [11][12][13], and it likely is soluble testicular bicarbonate-dependent adenylyl cyclase [14][15][16]. In several species, the -dependent increase in cAMP that occurs Ϫ HCO 3 during capacitation is implicated in the regulation of a phosphorylation cascade leading to the increase in protein tyrosine phosphorylation [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the full biologic and clinical significance of the differential distribution of ion channels in mammalian sperm remains to be elucidated fully, the importance of potassium and calcium-mediated signaling to sperm physiology remains undisputed (1,(32)(33)(34). Recent experimental evidence has linked murine sperm membrane hyperpolarization mediated by voltage-gated potassium channels to the acquisition of calcium signaling required for normal sperm function (4,35,36).…”
Section: Discussionmentioning
confidence: 98%
“…All Western blot analyses were essentially performed as previously described [6]. Anti-GFP antibody was used at 1/1000 dilution, and the goat anti-rabbit FITC conjugated secondary antibody was used at 1/2000 dilution.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Within the reproductive field, ROS have been implicated in male infertility and the redox regulation of tyrosine phosphorylation during sperm capacitation in a variety of species, including humans [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%